GUIDING MECHANISM WITH ALEXA VOICE SERVICE AND LINE FOLLOWER - Shawn Thomas; Snehal Durge; Tanmayee Suryawansh (International Journal of Innovations in Engineering Research and Technology, 2021)
The guiding mechanism is the main part of the our Project since it replaces the job of the guides by taking guided steps that are fed to the robot guide in the form of data into the program. It guides us to the required destination by moving with the help of wheels. The Robot Guide is a very friendly guide that helps the students to find a particular subject book in the library since it’s arobot at the end of the day. The processor in which we dump the program is also known as the "brain" which is run by a computer program. The program is very detailed as it gives commands for the moving parts of the robot to follow. There are many mechanical parts that are used in this part such as motors, wheels, and gears that make the robot move and turn. We also have a use of sensors to tell the robot about its surroundings. Sensors such as IR sensor which detects the black line and further guides the student to the shelves of the library. Alexa is a virtual assistant that was programmed and developed by Amazon and is available on almost all the wide range of products that are manufactured by Amazon, right from Amazon echo dot to Amazon FIRE TV. Alexa can be used for various tasks from a basic interaction with an AI, listening Music, listening to audiobooks, playing podcasts, for knowing weather forecast etc.